Opening schools and closing prisons: caring for destitute and delinquent children in Scotland 1812-1872 - Ralston, Andrew G. (Routledge studies in modern British history, 2017)
Preface -- Punishment, reformation and prevention : changing attitudes to juvenile crime in mid-nineteenth century Britain -- The lamentable extent of youthful depravity : the Tron Riot of 1812 -- Stirrings for change : developments in Edinburgh, 1812-1846 -- "An intermediate step" : the Glasgow house of refuge, 1838-1854 -- Prevention is better than cure : the Aberdeen industrial schools, 1841-1854 -- Ragged school rivalry : the original versus the united industrial school in Edinburgh, 1847-1854 -- "A better model" : the influence of the Scottish approach in England -- The formation of a national system (i) : reformatory and industrial schools legislation, 1854-1872 -- The formation of a national system (ii) : the effects of legislation on individual schools -- Schooling for all : industrial schools and the 1872 Education Act -- Change and continuity : nineteenth century approaches in context -- Bibliography -- Index